Effect of Extraction Time on Dried Form and Powder of Cardamom Seeds in Aqueous Solvent on Physical, Total Phenol, and Flavonoid Properties - Nurul Latifasari; Faizah Faizah; Ajeng Dyah Kurniawati (Journal of Applied Food Technology, 2024)
Cardamom seed spice is a plant that has bioactive components which are thought to be able to act as a natural antioxidant, so it has the potential to be a natural food additive in functional food products. These bioactive components can be obtained by extraction method using distilled water as a solvent. However, there have not been many studies regarding the effect of the extraction time used. Therefore, this research aims to determine the effect of the extraction time of cardamom seeds in simplicia and powder form on the physical properties, total phenols and total flavonoids. The extraction method used is maceration with extraction time levels of 5 minutes, 7 minutes and 9 minutes using distilled water as a solvent. The extract obtained will be tested for physical, qualitative and quantitative properties of total phenols and total flavonoids. The research results show that cardamom seed extract contains phenolics and flavonoids compound with different strengths and the extract color is brownish yellow. The resulting yield was 27.14% with the highest of total phenols 168,796 µg/mL and total flavonoids 38,564 µg/mL in the treatment of cardamom seed powder extraction time of 9 minutes. Cardamom seed powder extract prepared with an extraction time of 9 minutes is more capable of extracting bioactive components compared to other time levels and simplicia form.